Modeling of the structure of expenditure liabilities of municipalities - E. F. Nikitskaya; M. A. Valishvili (Путеводитель предпринимателя)
The article considers the system of rationing budgetfunds at the municipal level, aimed at increasing the budget provision. The authors substantiate the options for economic modeling of the cost of municipal services provided at the expense of the budgets of municipalities by the example of the Moscow region.